Engineered microenvironments for MSCs storage at ambient temperature in alginate core-shell capsules - Hubenia, Oleksandra; Leal-Marin, Sara; Trufanova, Natalia; Glasmacher, Birgit; Petrenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):235